Recent developments in surface-enhanced Raman spectroscopy in the field of chemical, biochemical and clinical application? a critical review - Balasubramani S.R.; Nagappan K.; Ewe L.S.; Viswanathan K.; Yew W.K.; Thiraviam S.G.; Sadana S.; Samuel T.K.D.; Kamalakannan K. (Taylor and Francis Ltd., 2025)
To comprehend the complex messages of science, we require visual senses for better understanding. It is evident that our visualisation falls short at minute levels. Surface Enhanced Raman Spectroscopy (SERS) facilitates the temporal identification and characterisation of the molecular composition, structure, and dynamics of a given sample. This technology promises to be an effective solution for many undiscovered and unaccounted outcomes in the chemical, biochemical, and clinical fields. Hence, early detection of large panels of bio targets, contaminants, and toxins is assessed with high levels of sensitivity and multiplexity, tracing to the extent of Nano (10?9) levels. Over the past decade, nanomaterials-based SERS has emerged, shedding light on the importance of different dimensions of nanomaterials, primarily in the development of SERS sensing for various applications. SERS Nano probes offer remarkable improvements by focusing and imaging, utilising the Raman scattering efficiency, wherein molecules are absorbed on a nanostructured surface. This article elucidates the SERS principle, classification based on sensing dimensions, and its application in the field of food safety and drug monitoring, detecting various proteins, viruses, and bacteria, both in-vitro and in-vivo imaging, cancer biomarker detection, as well as detecting nutrients, pesticides, and foodborne pathogens by SERS. It serves as a collective review of recent advancements that have flourished in the past few years, highlighting concepts, issues, and challenges with the prior motive of incorporating and stimulating wider interest in developing SERS nanomaterial applications for chemical engineering. ? 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.